The fix. Volume one, Where beagles dare - Spencer, Nick (Image Comics, Inc., 2016)
"The Eisner Award-nominated team behind Superior Foes of Spider-Man, bestselling writer Nick Spener (Morning Glories) and artist Steve Lieber (Detective Comics, Whiteout) are in cahoots again for an all-new, ongoing crime series, The Fix. The Fix is a story of the crooked cops, scheming mobsters, and corrupt politicians that run Los Angeles - and the sex toy that can bring them all down. Oh, and the hero is a drug-sniffing beagle named Pretzels"--Back cover.